1988
DOI: 10.1093/geronj/43.2.p40
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Role of a Structured Life Review Process in Homebound Elderly Subjects

Abstract: This study examined the therapeutic role of a structured life review process in a randomly selected group of 60 homebound elderly subjects. Subjects were placed in three groups and tested on four dependent variables at the beginning and end of an 8-week period. These variables were life satisfaction, psychological well-being, depression, and activities of daily living (ADL). One group, the experimental group, received the treatment of life review process; another, the control group, received a friendly visit; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
140
2
3

Year Published

1990
1990
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(149 citation statements)
references
References 13 publications
4
140
2
3
Order By: Relevance
“…Among 20 homebound older adults receiving six 1-hour life review sessions, Haight (1988) found significant increases in life satisfaction, psychological well-being, and activities of daily living scores, although there was no change in level of depression as measured by the Zung Self-Rating Depression Scale. Haight and Dias (1992) examined the process and outcomes of four types of reminiscence therapy in 8 weekly sessions.…”
Section: Related Literaturementioning
confidence: 87%
“…Among 20 homebound older adults receiving six 1-hour life review sessions, Haight (1988) found significant increases in life satisfaction, psychological well-being, and activities of daily living scores, although there was no change in level of depression as measured by the Zung Self-Rating Depression Scale. Haight and Dias (1992) examined the process and outcomes of four types of reminiscence therapy in 8 weekly sessions.…”
Section: Related Literaturementioning
confidence: 87%
“…(Butler, 1974;Coleman, 1992;Wong, 1989;Wong & Watt, 1991). Reminiscence may help older adults by focusing on former successful coping experiences (Wong, 1995), by reinforcing a sense of continuity (Parker, 1999), by finding meaning and coherence in one's life (Birren, 1987, Watt & Cappeliez, 2000 and by promoting reconciliation (Coleman, 1999) and by resolving hitherto unresolved conflicts (Butler, 1974;Haight, 1988). Many studies have tested the effects of reminiscence interventions on psychological wellbeing in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, although the distinction between reminiscence and life review is crucial, even the label of life review covers a large variety of interventions and these interventions can have very different theoretical underpinnings. For example, the intervention used by Haight et al (1988) is based on the work of Butler (1963). Serrano et al (2004) developed their intervention on the basis of recent research into autobiographical memories of depressed people.…”
Section: Discussionmentioning
confidence: 99%
“…Reminiscence may be a good method to improve the service uptake and treatment of depressed elderly, as it is an attractive, non-stigmatizing, and easy to administer intervention (Bohlmeijer, Smit & Cuijpers, 2003;Haight, 1988;Watt & Cappeliez, 2000). In this type of intervention elderly are asked to systematically review their lives on the basis of questions about their past (Haight, 1988;Watt & Cappeliez, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In this type of intervention elderly are asked to systematically review their lives on the basis of questions about their past (Haight, 1988;Watt & Cappeliez, 2000). Resolving conflicts from the past and making up the balance of one's life are important goals (Butler, 1963).…”
Section: Introductionmentioning
confidence: 99%